Re-description of the braincase of the rebbachisaurid sauropod Limaysaurus tessonei and novel endocranial information based on CT scans - PAULINA-CARABAJAL,ARIANA (2021)
Abstract CT scans of the type braincase of Limaysaurus tessonei (MUCPv-205) allowed the first study of the endocranial cavities (brain and inner ear) for this South American taxon. Comparisons of the cranial endocast of L. tessonei with other sauropods indicate that 1) South American rebbachisaurids are more similar to each other than to Nigersaurus, and 2) certain association of traits are present in all known rebbachisaurid cranial endocasts, such as lack of an enlarged dorsal expansion, poorly laterally projected cerebral hemispheres, presence of a small flocculus of the cerebellum, markedly long passage for the facial nerve (CN VII), markedly inclined pituitary, and presence of a passage for the basilar artery communicating the floor of the endocranial cavity and the pituitary fossa. The relatively enlarged olfactory region indicates that smell was an important sense for this group of dinosaurs, suggesting different olfactory capabilities when compared to coeval titanosaurs.